Raktātalyā samudrācaṃ udhāṇa - Sāsaṇe, Bhārata (Dilīparāja Prakāśana Prā. Li., 2022)
Articles; chiefly on Marathi literature.
Keywords: Aufsatzsammlung; Marathi literature; History and criticism.; Marathi literature